Effect of Film Thickness on Postharvest Ripening and Quality Characteristics of Tomato (Lycopersicon esculentum L.) Fruit Under Modified Atmosphere Packaging - Mathooko, Francis, M; Nabawanuka, Jane (Africa Jounals Online, 2003)
Two different gauges, (0.04mm and 0.08mm) of low density polyethylene (LDPE) films were tested for their effectiveness in controlling ripening and quality of tomato (Lycopersicon esculentum L. cv. Cal J) fruit during modified atmosphere packaging (MAP) under ambient conditions of 60 to 65% relative humidity and 26 ± 1°C. Control fruits were stored under similar ambient conditions. Fruits stored in polymeric bags remained green for the 12 days of the experiment and had lower percent weight loss compared to the control fruit. Film thickness had a significant effect (p<0.05) on degradation of chlorophyll, physical colour development, synthesis of lycopene and modified atmosphere development while it had little effect on weight loss and extent of fruit spoilage. Carbon dioxide concentration in the 0.08mm LDPE bags was twice that in 0.04mm bags while oxygen concentration was lower in the 0.08mm bags. MAP delayed the increase in ascorbic acid that is associated with ripening. Fruits in 0.08mm bags had slightly lower ascorbic acid content and total titratable acidity (TTA) than those in the 0.04mm bags. MAP itself had no effect on total solids content. Upon transfer to normal atmosphere, fruits previously held in MAP ripened normally with the changes for fruits previously in 0.08mm bags being slower. These results indicate that when all other parameters are held constant, a thicker film is more effective in retarding ripening processes and extending fruit shelf life, thereby facilitating handling and reducing waste.
Keywords: Low density polyethylene, Lycopersicon esculentum L., Modified atmosphere packaging, Tomato fruit.